Core Polarization Effects on the Inelastic Longitudinal Electron Scattering Form Factors of Ti 48,50 and Cr 52,54 nuclei - Flaiyh , Ghaith Naima (Iraqi Journal of Science, 2022)
In this paper, inelastic longitudinal electron scattering form factors C2 and C4transitions have been studied in Ti 48,50and Cr 52,54nuclei with the aid of shellmodel calculations. The core polarization transition density was evaluated byadopting the shape of Tassie model togther with the derived form of the ground statetwo-body charge density distributions (2BCDD's). The following transitions havebeen investigated; 0 2 2 2 1 1   and 0 2 4 2 1 1   of Ti 48 , 0 3 2 3 1 1   and0 3 4 3 1 1   of Ti 50 , 0 2 2 2 1 1   and 0 2 4 2 1 1   of Cr 52 and0 3 2 3 1 1   and 0 3 4 3 1 1   of Cr 54 nuclei. It is found that the corepolarization effects, which represent the collective modes, are essential forreproducing a remarkable agreement between the calculated inelastic longitudinalC2 and C4 form factors and those of experimental data.